The Relationship Between the Yo-Yo Tests, Anaerobic Performance and Aerobic Performance in Young Soccer Players - Karakoç, Barış (Akademia Wychowania Fizycznego w Katowicach, 2012)
The purposes of this study were to determine the relationship between performance in the Yo-Yo intermittent recovery test level 1 (YIRT1), the Yo-Yo intermittent recovery test level 2 (YIRT2) and the Yo-Yo endurance test (continuous) (YET) with maximal oxygen uptake (VO(2)max) and Wingate anaerobic performance (WaNT) test results in young soccer players (age 15.00 ± 0.0 years, body height 176.3 ± 4.2 cm and body mass 68.1 ± 3.6 kg). An ergospirometry device was used during the treadmill test (TRT) to determine VO(2)max. At the end of the study, significant differences were found between the Yo-Yo tests and TRT in terms of HRmax (TRT = 195,92, YIRT1 = 197,83, YIRT2 = 198,5 YET = 198) (p > 0.05). While there were moderate correlations between VO(2)max and YIRT 1–2 performances (respectively, r = 0.56, r = 0.53), there was only a weak relationship between VO(2)max and YET performance (r = 0.43) (distance covered). There were also moderate significant negative correlations between performance in the YIRT2 and peak power measured in the WaNT (r = −0.55), although there were no significant correlations between performance in the three tests and average power. A moderate negative correlation was found between performance in the YIRT2 and Fatigue index (FI) (r = −0,66). In conclusion, the YIRT2 may be a more suitable field test for determining both aerobic and anaerobic performance in soccer players.